Interpodes: Poland, Tom Keneally and Australian Literary History - Sharrad, Paul (Text Matters: A Journal of Literature, Theory and Culture, 2012)
This article is framed by a wider interest in how literary careers are made: what mechanisms other than the personal/biographical and the text-centred evaluations of scholars influence a writer’s choices in persisting in building a succession of works that are both varied and yet form a consistently recognizable “brand.” Translation is one element in the wider network of “machinery” that makes modern literary publishing. It is a marker of success that might well keep authors going despite lack of sales or negative reviews at home. Translation rights can provide useful supplementary funds to sustain a writer’s output. Access to new markets overseas might also inspire interest in countries and topics other than their usual focus or the demands of their home market. The Australian novelist and playwright Thomas Keneally achieved a critical regard for fictions of Australian history within a nationalist cultural resurgence, but to make a living as a writer he had to keep one eye on overseas markets as well. While his work on European topics has not always been celebrated at home, he has continued to write about them and to find readers in languages other than English. Poland features in a number of Keneally’s books and is one of the leading sources of translation for his work. The article explores possible causes and effects around this fact, and surveys some reader responses from Poland. It notes the connections that Keneally’s Catholic background and activist sympathies allow to modern Polish history and assesses the central place of his Booker-winning Schindler’s Ark filmed as Schindler’s List.